N6-methyladenosine reader YTHDF family in biological processes: Structures, roles, and mechanisms - Chen, Lin; Gao, Yang; Xu, Simiao; Yuan, Jinxiong; Wang, Min; Li, Tianyu; Gong, Jun (Frontiers in Immunology, 2023)
As the most abundant and conserved internal modification in eukaryote RNAs, N6-methyladenosine (m6A) is involved in a wide range of physiological and pathological processes. The YT521-B homology (YTH) domain families (YTHDFs) including YTHDF1, YTHDF2, and YTHDF3, are a class of cytoplasmic m6A-binding proteins defined by the vertebrate YTH domain, and exert extensive functions in regulating RNA destiny. Distinct expression patterns of the YTHDFs in specific cell types or developmental stages result in prominent differences in a variety of biological processes, such as stem cell fate, fat metabolism, embryonic development, neuromodulation, cardiovascular effect, infection, immunity, and tumorigenesis. Although the YTHDF family mediates tumor proliferation, metastasis, metabolism, drug resistance, and immunity, therapies targeting the YTHDF family have been underappreciated. In this review, we describe the structure of the YTHDF family and its functions in regulating RNA translation and degradation, focus on the roles and application value of the YTHDF family in biological processes, especially in tumors, and discuss the limitations and future research directions of the YTHDF family.